Development of Large-Horned Cattle Breeding in the Republic of Karakalpakstan and its Territorial Characteristics (Eurasian Journal of History, Geography and Economics, 2023)
The dynamics of cattle breeding in the Republic of Karakalpakstan and issues of its territorial organization are studied in this article